Optimasi Formula Masker Gel Peel Off Ekstrak Buah Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl ) Dengan Variasi PVA Dan HPMC Menggunakan Metode Simplex Lattice Design - Nurul Hidayati; Nanik Widyiastuti; Sutaryono (CERATA Jurnal Ilmu Farmasi, 2019)
Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl) is an effectiveplant against bacteria the causes of acne. To facilitate the application, it formulated in a peel off gel mask preparation. This study aims to determine the effect of the concentration of PVA as film forming and HPMC as a gelling agent on the physical properties of the peel off gel mask and determine the concentration of PVA and HPMC which produce the optimum formula.The Mahkota Dewa fruit was extracted by soxletation with ethanol 70%. The extract was made into 5 runs with variations in the concentration of PVA (10-16%) and HPMC (2-4%). The fifth run in the test of physical properties include organoleptic tests, homogenity, pH, viscosity, spreadability, adhesion and drying time. The optimum formula of peel off gel mask is obtained from software design expert version 6.0.8. simplex lattice design method with the studied response to viscosity, spreadability, and drying time.The results show that increasing the concentration of PVA can increase viscosity and drying time, and increasing the concentration of HPMC can increase the value of dispersion of the preparation. The optimum formula was obtained with a variation of PVA 13.09% and HPMC of 2.97%.